ANALYSIS OF LEGOWO ROW PLANTING SYSTEM AND SYSTEM OF RICE INTENSIFICATION (SRI) OF PADDY FIELD (ORYZA SATIVA L.) TOWARD GROWTH AND PRODUCTION - M. Darmawan (Universitas Sembilanbelas November Kolaka, 2016)
Rice is the main commodity crops in the province of Gorontalo, in addition to maize and pulses. One alternative technology to increase productivity is through application of Legowo cropping system that is engineered way of planting the tiles so that there is a spacious room extends to one direction between two rows of rice plants, while the other way seemed more tightly. In rice cultivation with system of transplanting, planting distance is one factor of production that is very important because it determines the productivity achieved. This research is expected to be a reference for farmers, especially in the province of Gorontalo to carry rice cultivation so as to increase the production of rice plants. The design of the study is a Randomized Complete Block Design by comparing between systems that are often used by farmers, namely row planting system tiles (S0), the system of row planting Legowo (2: 1) (S1), system of row planting Legowo (4: 1 ) (S2), planting system SRI (S3). The parameters of observations made were plant height, number of tillers, production (kg/plot), and observations of soil samplesman. The results showed treatment plant system of tiles provide number of tiller and height of plants that are best compared with other treatments. The best results for a number of productive tillers, the average production of grain/plot, grain weight of 1000 grain was in the treatment plant system Legowo row 2: 1.